Micro Site Characters Vis-a-vis Rooting Behaviour in Sal (Shorea robusta) - Dabral, B. G.; Pant, S. P.; Pharasi, S. C. (Indian Forester, 1984)
The paper details the rooting behaviour in Sal (Shorea robusta) tree at a site having compacted soil and with a hard pan formation. The tap-root extended upto 1.2 m only. Lateral roots extended upto a length of about 12 m in the direction of a 'nala', thereby sbowing that with shallow tap-root, long lateral roots running parallel to the soli layers get formed, to meet the water needs of the tree especially in hot dry season.